Evaluation of Charge-Discharge Characteristic of Lithium Cobalt Nickel Manganese Oxide for High-Energy Density Lithium-Ion Batte - Salehen, P.M.W.; Razali, H.; Sopian, K.; Lee, T.K.; Su'ait, M.S. (Journal of the Society of Automotive Engineers Malaysia, 2021)
The development of suitable cathode materials of lithium ion batteries (LIBs) for energy storage towards improving the performance of LIBs in order to meet the increasing demand globally is one of the challenges. This paper investigates the charge-discharge characteristic for lithium ion batteries developed focusing on cathode materials of LiNiCoMnO2 (NCM) – layered structured material with lithium anode. It also discusses the characteristic features of charge-discharge profile, optimized charge-end voltage as well as discharged limit voltage with a constant current C-rate with 0.1C, 0.3C and 0.5C. The coin cells were fabricated in a glove box full of argon gas using those cathode and anode with separator and organic electrolyte (1M LiPF6, EC: DEC 1:1). The performance of charge-discharge test was conducted with NEWARE tester equipment BTS 3000. This includes obtaining experimental data charge- discharge and power capacity to improve the performance of battery. Thus it is reported that charge-discharge characteristic of LNCM material is important to be analysed for LIBs. The parameter attained is vital and necessary enhancement work for the resolution of optimization BMS simulation.